Negotiating the TPP: Malaysia’s trade strategy from a neoclassical realist perspective - Nur Farhana Abd Khalid; Sufian Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to explain Malaysia’s approach to the Trans-Pacific Partnership (TPP) negotiations through a two-level neoclassical realism (NCR) lens. While structural factors such as economic structure and economic vulnerability shaped the broader context of Malaysia’s participation in the negotiations, this study argues that it is domestic political imperatives, in this case, elite legitimation, that ultimately determined the state’s negotiation strategy. Malaysia initially embraced the agreement under Prime Minister Najib Razak’s Barisan Nasional (BN) administration to boost Malaysia’s economy through trade liberalisation. This in 2017 shifted following the U.S. withdrawal and in 2018 following the succession of Prime Minister Mahathir Mohamad, who is historically more opposed to economic liberalism, when he called for a review of certain sensitive provisions that could threaten the Bumiputera framework and domestic policies. Our findings suggest that this pragmatic yet fluctuating approach was shaped by Malaysia’s successive ruling elites’ converged performance and particularistic legitimation, supported by procedural legitimation. First, performance-based legitimation was achieved by emphasising the economic benefits. Second, particularistic legitimation was boosted through the protection of Bumiputera privileges in sensitive sectors such as government procurement and state-owned enterprises. Additionally, both pathways were shaped by procedural legitimation, which was attained by maintaining public confidence and securing electoral support. By situating Malaysia’s TPP negotiations within this framework, our study contributes to the literature on domestic political influences in foreign economic policymaking, particularly in Southeast Asia. As such, it highlights how domestic political considerations shape trade strategies beyond structural factors.